Building materials from cellular concrete and their production technologies - Zhalgasov, Марат; Baydakova, Арна (Рroblems of engineering and professional education, 2023)
In the article the expediency of use in modern construction materials obtained from cellular concrete autoclaved, by reducing the cost of heating, the absorption of ambient sounds, light weight, high frost resistance and good adhesion.